The Effectiveness of Customer Loyalty Program in Malaysian Retail Industries - Thela, Rendy Yudistira (2008)
Customer loyalty has become a major theme in marketing research since the 20th century. While there are many loyalty programmes in the today’s market place in retail service industries, the effectiveness of such programmes has always been debatable. Hence this study intends to examine the effectiveness of a sample of services firms which offer loyalty programmes to their customers. This research is performed by using a quantitative methodology. There are three samples of firms in the retail services sector in Malaysia that is used as the subject for this study. Those sample firms are Isetan, Jusco and Tesco. The survey for this research was survey was conducted on 180 customers in the loyalty program with questions on the real perception and use of the customer loyalty programmes. Moreover, the result of the finding in this research is analyzed by using regression prediction models. The result of this finding has shown that the negative customer behaviour and perception towards the loyalty program will hold back the effectiveness of the customer loyalty program.